SIKAP MAHASISWA JURUSAN PENDIDIKAN LUAR BIASA TERHADAP PROFESI GURU PENDIDIKAN LUAR BIASA - Asep Supena (Perspektif Ilmu Pendidikan, 2009)
The main purpose of this study was to describe how student’s attitude toward the profession of special education teacher Next, this study also wantsed to know the student’s attitude based on different characteristics, ie, sex, length of study in special education department, the priority of the student’s choice of studied in State University of Jakarta. The population icovered all students in special education Departement of School of Education, State University of Jakarta. The respondents were chosen randomly with total number of 137 students. Questionnaire were distributed to the students as survey method implemented. The result of study indicated that all responding have positive attitude toward the PLB‘s teacher works. In details, the more senior students in Special Education Department, the more positive their attitude toward PLB‘s teacher’s profession. The students who choose this Department as their first choice in State University of Jakarta tend to have more positive attitude towards the profession of special education teacher. Female students‘ attitude is more positive toward the profession of special education teacheris more positive than male student‘s attitude. Then, nonregular students attitude are more positive toward the profession of special education teacher than regular students attitude. Finally, students who are teaching non-special education subjects are more positive towards the profession of special education teacher